Emotion dysregulation in adolescents is normalized by ADHD pharmacological treatment - Krisztina Kondi; Mária Takács; Evelyn Kovács-Posta; Claudia Szajli; Tünde Sebők-Welker; János M. Réthelyi; Nóra Bunford (Borderline Personality Disorder and Emotion Dysregulation)
Abstract Background Attention-deficit/hyperactivity disorder (ADHD) is associated with emotion dysregulation (ED) and in ADHD, beyond ADHD and comorbidity severity, ED confers increased risk for negative outcomes. First- and second-line ADHD pharmacotherapy is effective at ameliorating core symptoms and improving cognitive functioning and accumulating evidence indicates primairly in children and adults, active ADHD pharmacotherapy has beneficial effects on emotional symptoms. Gaps in knowledge remain about whether in adolescents, ADHD pharmacotherapy has beneficial effects on ED or about the extent to which effects are apparent for discontinued/ past ADHD pharmacotherapy. Methods Examined, in N = 297 adolescents (M age=15.77 years, SD = 1.06; 39.06% girls; n = 86 classified as with ADHD), whether accounting for depression and oppositional symptoms, concurrent and 18-month prospective measures of parent- and self-reported ED (1) differ across adolescents without ADHD, medication-naïve adolescents with ADHD, and ever-medicated (currently or previously) adolescents with ADHD. Results In case of parent-reported ED, ever medicated adolescents with ADHD exhibited a decline in ED over time whereas adolescents without ADHD and never medicated adolescents with ADHD exhibited no changes in ED over time. In case of self-reported ED, ever-medicated adolescents with ADHD exhibited lower ED than never medicated adolescents with ADHD and never medicated adolescents with ADHD exhibited greater ED than adolescents without ADHD. Currently and previously (but not currently) medicated adolescents did not differ in ED. Across parent- and self-reported findings, observed pattern of results held when analyses focused on adolescents who did not change medication status between baseline and follow-up. Conclusions ADHD pharmacotherapy may have a boosting effect on longitudinal changes in parent-reported ED and a normalizing effect on concurrent measures of self-reported ED in adolescents.